DAMPAK NOM, APYD, NPF PADA ROA UNIT USAHA SYARIAH PERBANKAN MASA PANDEMIK COVID-19 2020-2021 - R. Deden Adhianto (POLITEKNIK PIKSI GANESHA, 2022)
Abstract Even during the Covid-19 pandemic, sharia banking business units still need to increase their business capital. This must be done in order to fulfill the requirements to become a sharia commercial bank in 2023. One of the capital additions comes from income, and the ROA ratio is used as a measuring tool. The higher the ROA value obtained, the better. The purpose of this study relates to whether the variables NOM, APYD and NPF have an impact on the ROA variable either simultaneously or partially. For data collection research variables, used purposive sampling method. The data comes from the achievement of the financial performance of the national sharia banking business unit for the period March 2020 - May 2021 which was compiled by the Financial Services Authority. The research was conducted using multiple linear regression and processed by SPSS software. The results of the research conducted showed that the variables NOM, APYD and NPF simultaneously had a significant effect on the ROA variable. While partially the NOM variable has a significant influence on the ROA variable. However, each of the APYD and NPF variables partially does not have a significant effect on the ROA variable. Keywords : NOM, APYD, NPF, ROA